THE EFFECT OF HEALTH EDUCATION ON KNOWLEDGE OF MORINGA LEAF UTILIZATION FOR STUNTING PREVENTION AMONG TODDLERS - dhita kris prasetyanti; Halimatus Saidah; Meirna Eka Fitriasnani; Sutrisni; Putri Wahyu Wigati; Oktafia Sukmawati (Nursing Sciences Journal, 2026)
Stunting remains a nutritional problem among toddlers, influenced by low parental knowledge regarding the utilization of nutritious local foods. Moringa leaves (Moringa oleifera) have a high nutritional content and potential to be used as an alternative for stunting prevention. This study aimed to determine the effect of health education on knowledge regarding the utilization of Moringa leaves as an effort to prevent stunting among toddlers. The study employed a pre-experimental method with a one-group pretest–posttest design. The study population consisted of 30 respondents selected using purposive sampling. Knowledge was measured before and after the provision of health education. Data analysis was conducted using the Wilcoxon test. The results showed that before health education, all respondents (100%) had poor knowledge. After the intervention, most respondents had good knowledge (28 respondents; 93.3%), while 2 respondents (6.67%) had sufficient knowledge. The Wilcoxon test results indicated a p-value of 0.000 (p < 0.05), demonstrating a significant difference in knowledge before and after the health education intervention. It can be concluded that health education has a significant effect on improving knowledge regarding the utilization of Moringa leaves as an effort to prevent stunting among toddlers.